2023
DOI: 10.3390/microorganisms11020521
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Virulence Potential, and Growth in Cheese of Bacillus cereus Strains Isolated from Fresh and Short-Ripened Cheeses Sold on the Italian Market

Abstract: This study investigated B. cereus presence in 122 samples belonging to 34 typologies of fresh or short-ripened cheeses made from cow, sheep, goat, or buffalo pasteurized milk, and sold on the Italian market. B. cereus was isolated at a prevalence of 9.8%, with a marked variability among cheese categories, and at low counts (always below 2.26 Log CFU/g). Twelve isolates were identified by MALDI-TOF analysis and typified by RAPD PCR as belonging to different B. cereus strains. All the strains were tested for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…In opposite to our result, Adam et al (2021 ) and Fetouh et al . (2022 ) indicated that the occurrence of B. cereus in yogurt samples was at 8.0%, and 4.0%, respectively, while it could not be detected in yogurt samples by Tirloni et al (2017 ). The absence of growth or even low incidence observed might be owing to the low pH < 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In opposite to our result, Adam et al (2021 ) and Fetouh et al . (2022 ) indicated that the occurrence of B. cereus in yogurt samples was at 8.0%, and 4.0%, respectively, while it could not be detected in yogurt samples by Tirloni et al (2017 ). The absence of growth or even low incidence observed might be owing to the low pH < 5.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, variation in B. cereus rate is owing to different bacterial loads and poor hygiene standards during the preparation and production process. Bacillus cereus is recurrently isolated from raw milk because of pasteurization process resistance ( Tirloni et al , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…are often found in dairy farm environments (soil, feed, udders, and milk) [45,46]. They can also be frequently found in artisanal and commercial ewe's milk cheese [47,48]. The high resistance of Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus cereus is an important foodborne pathogen that is ubiquitous in nature and can be isolated from many different foods and food ingredients [8,9]. In 2018, the EU had 98 foodborne illness outbreaks, with B. cereus ranking fifth behind Salmonella (Salmon 1885), Campylobacter (Marshall et al 1983), norovirus (Kapikian 1972), and Staphylococcus aureus (Ogston.…”
Section: Introductionmentioning
confidence: 99%